2018
DOI: 10.1101/386367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dendritic spine geometry and spine apparatus organization govern the spatiotemporal dynamics of calcium

Abstract: Dendritic spines are small subcompartments that protrude from the dendrites of neurons and are important for signaling activity and synaptic communication. These subcompartments have been characterized to have different shapes. While it is known that these shapes are associated with spine function, the specific nature of these shape-function relationships is not well understood. In this work, we systematically investigated the relationship between the shape and size of both the spine head and spine apparatus, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 122 publications
2
29
0
Order By: Relevance
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [59]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [41,53,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [59]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [41,53,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…10, see also Movie S1 available online. Because the goal of this simulation was not to show biological accuracy, but rather to demonstrate that our pipeline is capable of producing biophysically relevant FEA simulations, we use a simplified version of the model found in Bell et al [53].…”
Section: Simulating Reaction-diffusion In the Volumementioning
confidence: 99%
“…In addition to studying the spatiotemporal dynamics of cAMP in spines of different geometries, we also compare the peak time for each period, the peak concentration, and the Area Under the Curve (AUC) for each period. These metrics allow us to compare the oscillatory behaviors of cAMP in dendritic spines [35,36].…”
Section: Metrics For Camp/pka Dynamicsmentioning
confidence: 99%
“…Therefore, we chose a constant value of τ = 50 ms. Specialization of this model to Ca 2+ and cAM P can be found in Bell et al [50] and Ohadi et al [51,52], respectively.…”
Section: Governing Equationsmentioning
confidence: 99%